FTO Obesity Risk Variants Are Linked to Adipocyte IRX3 Expression and BMI of Children - Relevance of FTO Variants to Defend Body Weight in Lean Children? - Landgraf, Kathrin; Scholz, Markus; Kovacs, Peter; Kiess, Wieland; Körner, Antje (PloS one, 2016)
BACKGROUND Genome-wide association studies have identified variants within the FTO (fat mass and obesity associated) locus as the strongest predictors of obesity amongst all obesity-associated gene loci. Recent evidence suggests that variants in FTO directly affect human adipocyte function through targeting IRX3 and IRX5 and thermogenesis regulation. AIM We addressed the relevance of this proposed FTO-IRX pathway in adipose tissue (AT) of children. RESULTS Expression of IRX3 was higher in adipocytes compared to SVF. We found increased adipocyte-specific expression of IRX3 and IRX5 with the presence of the FTO risk haplotype in lean children, whereas it was unaffected by risk variants in obese peers. We further show that IRX3 expression was elevated in isolated adipocytes and AT of lean compared to obese children, particularly in UCP1-negative adipocytes, and inversely correlated with BMI SDS. Independent of BMI, IRX3 expression in adipocytes was significantly related to adipocyte hypertrophy, and subsequent associations with AT inflammation and HOMA-IR in the children. CONCLUSION One interpretation of our observation of FTO risk variants linked to IRX3 expression and adipocyte size restricted to lean children, along with the decreased IRX3 expression in obese compared to lean peers, may reflect a defense mechanism for protecting body-weight, which is pertinent for lean children.